Diet Hierarchies Guide Temporal-Spatial Variation in Drosophila suzukii Resource Use - Stockton, Dara G.; Loeb, Gregory M. (Frontiers in Ecology and Evolution, 2022)
Among insects, female oviposition preferences are critical to understanding the evolutionary dynamics between herbivores and hosts. Previous studies have shown Drosophila resource use has a strong genetic basis, although there is evidence that preferences are adaptable given isolation from ancestral hosts. Given the high degree of adaptability and behavioral plasticity of invasive species, we were interested in the mechanisms affecting host preferences of the invasive fruit fly, Drosophila suzukii, which in recent years has developed a nearly global range infesting small fruit crops. We studied the diet hierarchies of D. suzukii using a combination of laboratory and field assays designed to assess how female oviposition host choice differs given the availability of, and experience with, different fruit and non-fruit hosts. We found that host preferences did not shift over time and flies reared on two differential isolated diets up to F5 behaved and performed similarly regardless of diet lineage. Rather, female host choice appeared guided by a fixed hierarchical system of host preferences. Raspberry was more preferred to mushroom, which was more preferred to goose manure. However, if preferred resources were absent, the use of less-preferred resources was compensatory. We suggest that among niche specialists, such as D. suzukii, these hierarchies may support a bet-hedging strategy, rather than multiple-niche polymorphism, allowing for niche separation during periods of increased competition, while maintaining more diverse, ancestral feeding behaviors when preferred resources are scarce.